2020
DOI: 10.1002/int.22235
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing PROMETHEE method with intuitionistic fuzzy soft sets

Abstract: The notion of intuitionistic fuzzy soft sets (IFSSs) provides an effective tool for solving multiple attribute decision making with intuitionistic fuzzy information. The most crucial issue in decision making based on IFSSs is how to derive the ranking of alternatives from the information quantified in terms of intuitionistic fuzzy values. In this study, we propose a new extension of the preference ranking organization method for enrichment evaluation (PROMETHEE), by taking advantage of IFSSs. In addition to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(45 citation statements)
references
References 56 publications
0
38
0
Order By: Relevance
“…In that, subjective and objective weights of the criteria are calculated, and the described approach is highlighted. Feng et al [12] suggested the Enhancing PROMETHEE method and its optimization is determined by three linguistic preference structures. Intuitionistic fuzzy soft set (IFSS) based on similarity measures are also determined.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In that, subjective and objective weights of the criteria are calculated, and the described approach is highlighted. Feng et al [12] suggested the Enhancing PROMETHEE method and its optimization is determined by three linguistic preference structures. Intuitionistic fuzzy soft set (IFSS) based on similarity measures are also determined.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the above, the Extended PROMETHEE method is introduced by Feng et al [12] in the IFSS environment and is described as follows. Consider D = d 1 , d 2 , ...., d n , the set of alternatives and C = c 1 , c 2 , ...., c n , the set of criteria.…”
mentioning
confidence: 99%
“…In [6] the author also presented a new concept of soft set parametrization reduction. Several researchers have recently investigated the application of hybrid soft-set models in different systems, such as [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many researchers explored fixed point findings in soft metric type spaces (see, for example, [22][23][24][25]). Some results related to intuitionistic fuzzy soft sets were investigated in [26,27]. Recently, Alcantud [28] has discussed the properties of topological separability on soft setting.…”
Section: Introductionmentioning
confidence: 99%